PENGARUH DISKON DAN NIAT BELI TERHADAP KEPUTUSAN PEMBELIAN DI MARKETPLACE SHOPEE PADA MAHASISWA STIE TAMANSISWA BANJARNEGARA - Frina Annur, Yulia; Lustono, Lustono; Maesaroh, Siti (Perwira Journal of Economics & Business, 2023)
Shopee is one of the largest marketplaces in Indonesia. Various facilities are offered from this marketplace. Ranging from electronic goods, fashion to daily necessities are also available. The problem in this research is the increase in purchasing decisions at major Shopee events that offer big discounts. The purpose of this study was to determine the effect of discounts and purchase intentions partially and simultaneously on purchasing decisions in the Shopee marketplace for STIE Tamansiswa Banjarnegara students. This research uses quantitative methods. Data collection techniques by distributing questionnaires and research samples as many as 87 people. The analytical tools used are instrument test and classical assumption test. The data analysis technique used is multiple linear regression, t test, F test, and coefficient of determination test R square with the help of SPSS program. The results of this study indicate that partially discount (X1) has a significant positive effect on purchasing decisions and purchase intention (X2) has a significant positive effect on purchasing decisions. Then simultaneously discount and purchase intention have a significant positive effect on purchasing decisions. The value of the coefficient of determination R square is 57.9 percent of the purchasing decision variables influenced by the discount variable and purchase intention. While the remaining 42.1 percent is influenced by other variables not examined in this study. The conclusion in this study is that the higher the discount rate and purchase intention, the higher the purchasing decisions made by consumers.